Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/cge.13977
|View full text |Cite
|
Sign up to set email alerts
|

ANKRD11 variants: KBG syndrome and beyond

Abstract: Mutations affecting the transcriptional regulator Ankyrin Repeat Domain 11 (ANKRD11) are mainly associated with the multisystem developmental disorder known as KBG syndrome, but have also been identified in individuals with Cornelia de Lange syndrome (CdLS) and other developmental disorders caused by variants affecting different chromatin regulators. The extensive functional overlap of these proteins results in shared phenotypical features, which complicate the assessment of the clinical diagnosis. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…An incorrect genetic diagnosis can have severe consequences for prognostic and therapeutic management of the patient, and, as in this case, for the reproductive advice. Moreover, our findings seem to support recent evidences of age‐dependent phenotypic evolution in individuals harboring ANKRD11 variants (Parenti et al, 2021 ), and demonstrate the importance of including KBGS in the differential diagnosis of young children with CdLS features. Therefore, it is crucial to include ANKRD11 in gene panels used for molecular testing of individuals presenting with clinical characteristics of CdLS.…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…An incorrect genetic diagnosis can have severe consequences for prognostic and therapeutic management of the patient, and, as in this case, for the reproductive advice. Moreover, our findings seem to support recent evidences of age‐dependent phenotypic evolution in individuals harboring ANKRD11 variants (Parenti et al, 2021 ), and demonstrate the importance of including KBGS in the differential diagnosis of young children with CdLS features. Therefore, it is crucial to include ANKRD11 in gene panels used for molecular testing of individuals presenting with clinical characteristics of CdLS.…”
Section: Figuresupporting
confidence: 90%
“…Nevertheless, several studies have stressed the importance of a critical reconsideration of genetic results and a further implementation of protocols for variant‐level reevaluation and case‐level reanalysis (Deignan et al, 2019 ). This is especially relevant in the context of syndromes, such as the chromatinopathies Cornelia de Lange syndrome (CdLS, OMIM#122470) and KBG syndrome (KBGS, OMIM #148050), with overlapping phenotypes that may evolve over time (Parenti et al, 2021 ). Here, we present a challenging familiar case reanalyzed in which phenotypic features of both KBGS and CdLS are observed, and where genetic variants in ANKRD11 and NIPBL were identified.…”
Section: Figurementioning
confidence: 99%
“…Prior studies have noted that haploinsufficiency is the likely pathogenic mechanism in these cases based on the tightly regulated abundance of ANKRD11 during the cell cycle (Walz et al, 2015). Moreover, molecular analysis of cohorts of patients with KBG syndrome have found that the majority of ANKRD11 pathogenic variants are frameshift and nonsense variants leading to a loss‐of‐function, and presumably, haploinsufficiency as well (Gnazzo et al, 2020; Goldenberg et al, 2016; Loberti et al, 2022; Low et al, 2016; Parenti et al, 2021; Scarano et al, 2019). Recenty, functional studies performed on ANKRD11 missense variants found these decreased ANKRD11 stability and transcriptional activity, further supporting haploinsufficiency as a pathologic mechanism for KBG syndrome (de Boer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous single nucleotide variants and indels within ANKRD11 (OMIM #611192), which encodes ankyrin repeat domain 11, were found to cause KBG syndrome and heterozygous deletions at 16q24.3 that contain ANKRD11 have been shown to produce an overlapping clinical phenotype (Sacharow et al, 2012; Sirmaci et al, 2011). Larger case series have since established that KBG syndrome exhibits variable expressivity, and although no definitive genotype–phenotype correlations have been identified, individuals with microdeletions encompassing ANKRD11 and other surrounding genes appear to have an increased risk for neurologic involvement and a higher incidence of congenital heart defects, astigmatism, and thrombocytopenia (Goldenberg et al, 2016; Low et al, 2016; Novara et al, 2017; Parenti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation